NFC antenna for mobile phone and preparation method of electromagnetic wave absorbing material of them
A lightweight electromagnetic wave absorbing material layer composed of absorbing powder and polymer elastomer addresses weight and performance issues in NFC antennas, ensuring strong magnetic shielding and signal quality with improved impedance matching.
Patent Information
- Application Number
- JP2024112585
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-13
- Filing Date
- 2024-07-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Existing NFC antennas for mobile phones face issues with ferrite-based magnetic shielding materials that increase weight and volume, and amorphous and nanocrystalline alloys that have high saturation magnetization and poor impedance matching, leading to reduced signal quality and performance.
A thin, lightweight electromagnetic wave absorbing material layer made of electromagnetic wave absorbing powder and polymer elastomer, with a uniform particle size distribution, is applied between the NFC antenna body and metal bottom plate, enhancing magnetic shielding and impedance matching.
The solution provides strong magnetic shielding, improved signal quality, and cost-effective production, with the ability to process into various shapes, while maintaining mechanical stability and reliability.
Smart Images

Figure 2025013303000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of antennas, in particular to an NFC antenna for mobile phones and a method for preparing the electromagnetic wave absorbing material thereof. [Background technology]
[0002] An NFC antenna for mobile phones is a passive antenna that uses near-field communication technology (NFC) to communicate with other devices. NFC antennas generally use a coil antenna consisting of a conductor coil and a magnetic shielding material. NFC antennas for mobile phones usually have an NFC antenna body and a metal base plate, and metal reflects and absorbs radio waves, and the metal base plate interferes with the NFC signal, resulting in reduced signal quality. Therefore, in conventional technology, a magnetic shielding material is combined with the NFC antenna for mobile phones to suppress metal interference.
[0003] In the prior art, most of the magnetic shielding materials use ferrite (metal oxide) or amorphous, nanocrystalline (soft magnetic alloy). Patent Document 1 discloses a small NFC antenna in which the antenna assembly includes an FPC board, a conductor, and a ferrite sheet, and in use, the conductor is first inserted into an etched groove at the top end of the FPC board, then the ferrite sheet is placed on the top end of the FPC board, and finally the ferrite sheet is thermocompressed to complete the manufacture of the product. Patent Document 2 discloses an NFC antenna and tag that includes a PCB board, a metal bottom plate, a soft magnetic layer, and an NFC antenna body, in which the metal bottom plate is provided on the PCB board, the soft magnetic layer is provided on the metal bottom plate, and the NFC antenna body is provided on the soft magnetic layer.
[0004] Currently, the problem with using ferrite (metal oxide) as a magnetic shielding material for the NFC antenna of a mobile phone is that ferrite (metal oxide) is relatively heavy, which increases the weight and volume of the mobile phone. The manufacturing method uses a sintering method, which requires a temperature of 1100°C or higher, resulting in a low yield, and the die-cutting of ferrite contains scraps, which require covering the top and bottom with film and trimming, which increases the cost.
[0005] Currently, the problem with using amorphous and nanocrystalline (soft magnetic alloys) as magnetic shielding materials for NFC antennas in mobile phones is that soft magnetic alloys, which are typical magnetic loss absorption materials, have advantages such as high saturation magnetization, good temperature stability, and low cost, but they have a large complex dielectric constant and poor impedance matching, making it difficult to meet the performance requirements of electromagnetic wave absorption materials for 5G communications.
[0006] Therefore, an object of the present invention is to provide a new radio wave absorbing material for mobile phone NFC antennas, which is thin, lightweight, has strong magnetic shielding performance, effectively blocks metal interference with NFC antennas, and ensures the signal quality of the NFC antennas. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Chinese Patent Application No. CN202320076225.X [Patent Document 2] Chinese Patent Application No. CN202221616567.8 Summary of the Invention [Problem to be solved by the invention]
[0008] In order to overcome the above-mentioned shortcomings, the object of the present invention is to provide an NFC antenna for a mobile phone and a method for preparing an electromagnetic wave absorbing material thereof, which has a thin thickness, is lightweight, has strong magnetic shielding performance, effectively shields the metal interference with the NFC antenna, and can ensure the signal quality of the NFC antenna, and which is obtained by mixing the electromagnetic wave absorbing powder with a polymer elastomer in a flat spreading manner to form a uniform particle size distribution, and is easy to process into electromagnetic wave absorbing materials of various shapes, and which achieves high magnetic permeability, good impedance matching, stable electromagnetic wave absorption, and high reliability. [Means for solving the problem]
[0009] The object of the present invention is achieved by the following technical means.
[0010] An NFC antenna for a mobile phone, comprising an NFC antenna main body, an electromagnetic wave absorbing material layer, and a metal bottom plate, the electromagnetic wave absorbing material layer being provided on the metal bottom plate, the NFC antenna main body being provided on the electromagnetic wave absorbing material layer, the electromagnetic wave absorbing material layer being a film or sheet made of an electromagnetic wave absorbing material, the electromagnetic wave absorbing material containing electromagnetic wave absorbing powder and a polymer elastomer, the electromagnetic wave absorbing powder being a soft magnetic alloy or a soft magnetic composite material and having a two-dimensional sheet-like structure and being spread evenly within the polymer elastomer, and the mass ratio of the electromagnetic wave absorbing powder to the polymer elastomer being 10-20:1-5.
[0011] Currently, most "magnetic shielding materials" use ferrite (metal oxide) or amorphous nanocrystals (soft magnetic alloys), but the electromagnetic wave absorbing material used in the present invention is an electromagnetic wave absorbing powder with a two-dimensional sheet structure that is flatly laid on a polymer elastomer, and the electromagnetic wave absorbing powder has high saturation magnetic induction strength and low coercive force, which can effectively isolate electromagnetic interference and magnetic field interference and improve the magnetic shielding performance of the electromagnetic wave absorbing material layer. Compared with ferrite, the specific gravity of the electromagnetic wave absorbing material is small, which can significantly reduce the weight of the entire antenna structure and increase the weight ratio of the entire device. Compared with amorphous and nanocrystalline materials, the electromagnetic wave absorbing powder of the present invention is mixed with a polymer elastomer in a flat laying manner, thereby forming a uniform particle size distribution and making it easy to process into electromagnetic wave absorbing materials of various shapes. The polymer elastomer acts as a filler and binder within the electromagnetic wave absorbing material, uniformly dispersing the electromagnetic wave absorbing powder within the electromagnetic wave absorbing material and improving the magnetic shielding effect. In addition, the electromagnetic wave absorbing powder can be tightly bonded to the polymer elastomer, thereby increasing the mechanical strength and stability of the electromagnetic wave absorbing material.
[0012] In the above-mentioned NFC antenna for a mobile phone, the electromagnetic wave absorbing powder has a powder thickness of 0.5 to 1.5 μm and a particle diameter D50 range of 30 to 100 μm.
[0013] In the above-mentioned NFC antenna for a mobile phone, the soft magnetic alloy is at least one selected from the group consisting of an iron-silicon-aluminum soft magnetic alloy, an iron-silicon soft magnetic alloy, an iron-nickel soft magnetic alloy, an iron-nickel-molybdenum soft magnetic alloy, an iron-aluminum soft magnetic alloy, an iron-silicon-aluminum-nickel soft magnetic alloy, an iron-chromium soft magnetic alloy, and an iron-cobalt soft magnetic alloy.
[0014] Preferably, the soft magnetic alloy is an iron-silicon-aluminium soft magnetic alloy, also known as Sendust alloy, with the main components being Fe9.6-Si5.4-Al.
[0015] In the above-mentioned NFC antenna for mobile phone, the soft magnetic composite material has a two-dimensional sheet-like multilayer structure including, from the inside to the outside, a soft magnetic alloy, an Al2O3 layer, and an amorphous carbon layer.
[0016] The soft magnetic composite material uses a two-dimensional sheet-like multi-layer structure, in which an Al2O3 layer is provided between the soft magnetic alloy and the amorphous carbon layer, which not only prevents the generation of carbon nanomaterials on the surface of the soft magnetic composite material, but also introduces a multiple scattering and reflection mechanism to improve the microwave absorption properties. At the same time, this multi-layer structure can also act as a barrier protection and improve the corrosion resistance of the soft magnetic composite material.
[0017] In the above-mentioned NFC antenna for a mobile phone, the inductance value of the antenna coil of the NFC antenna main body is 1.6 to 2.0 μH.
[0018] By setting the inductance value of the antenna coil of the NFC antenna body to 1.6 to 2.0 μH, capacitance matching becomes easier to achieve.
[0019] Preferably, the metal base plate includes, but is not limited to, aluminum, copper, and stainless steel materials.
[0020] In addition, in the above-mentioned NFC antenna for mobile phones, the electromagnetic wave absorbing material is formed by laminating and laying out electromagnetic wave absorbing powder having a two-dimensional sheet-like structure, and by interposing a polymer elastomer between the electromagnetic wave absorbing powder to block it, no electrical continuity is formed in the electromagnetic wave absorbing powder.
[0021] The communication frequency in the industry is 13.56MHz. The structural design of the electromagnetic wave absorbing material makes it suitable for the frequency of 13.56MHz. When the electromagnetic wave absorbing powder is conductive, alloy flakes are formed, which has a very low permeability at 13.56MHz and is attenuated to less than 50% at 1MHz.
[0022] In the above-mentioned NFC antenna for a mobile phone, the polymer elastomer is at least one of polyurethane, acrylic acid, organosilicon, and epoxy resin.
[0023] Preferably, the polymeric elastomer is a polyurethane.
[0024] The present invention also relates to a method for preparing the electromagnetic wave absorbing material for the NFC antenna for a mobile phone, comprising the following steps S1 to S5: S1 raw material blend: Bulk density 0.2-0.7g / cm 3 , tap density 0.6~2.0g / cm 3 and a polymer elastomer to obtain a raw material mixture. S2 slurry stirring: adding the raw material mixture into a stirrer, then adding a solvent and auxiliary components, mixing the solvent, raw material mixture, and auxiliary components in a mass ratio of 40-80:10-50:0.5-2, and stirring thoroughly until homogenous, to produce a slurry with a viscosity of 1500-2000 mPa s; S3 Slurry application: the slurry is applied onto a protective film, and spread evenly on the protective film surface with a scraper, and the temperature of the application is set to 50 to 120°C and the speed is set to 0.5 to 4 m / min, and a dry film is obtained after drying; S4 Dry film lamination: The dried film is placed in a laminator, and the temperature is set to 150-180°C and the pressure is set to 10-20Mpa to densify the film to form an electromagnetic wave absorbing material; S5 Cutting: The process of cutting the laminated electromagnetic wave absorbing material according to the design requirements to obtain the required size and shape.
[0025] In the prior art, the preparation method of ferrite (metal oxide) used in NFC antennas for mobile phones to prevent metal interference uses a sintering method, the temperature is over 1100°C, the yield is low, and the die-cutting of ferrite contains scraps, so it is necessary to cover the top and bottom with films and trim the edges.
[0026] The method for preparing the electromagnetic wave absorbing material for NFC antennas of mobile phones of the present invention has lower costs, and in particular, in the case of an electromagnetic wave absorbing material with a magnetic permeability of 150 and a thickness of 0.08 mm, the cost can be reduced by 20%.
[0027] The electromagnetic wave absorbing material produced by the above preparation method is a flexible product, and can be designed into a variety of shapes compared to ferrite, etc., does not shed, does not require edging and double-sided coating, and can reduce processes and costs. The above preparation method for the electromagnetic wave absorbing material is simple, can be prepared on a large scale, and has a wide range of application scenarios in the field of electromagnetic wave absorbing materials.
[0028] In addition, compared with conventional manufacturing methods such as rolling and casting, there is a possibility that certain defects and gaps may exist inside the particles of the electromagnetic wave absorbing material and the polymer elastomer due to the compatibility between them. Therefore, the present invention uses the dry film lamination method of hot press molding to help form an electromagnetic wave absorbing material with a uniform particle size distribution.
[0029] Preferably, the protective film is a PET film.
[0030] The preparation method of the above electromagnetic wave absorbing material is simple, can be prepared on a large scale, and has a wide range of application scenarios.
[0031] In addition, in the above-mentioned method for preparing an electromagnetic wave absorbing material for an NFC antenna for a mobile phone, the solvent in S2 is any one of methyl isopropyl ketone, acetone, cyclohexanone, and DMF, and the auxiliary component is at least one of a dispersant, an antifoaming agent, a leveling agent, and a surfactant.
[0032] Preferably, the solvent is methyl isopropyl ketone, and the auxiliary components include dispersant BYK-110, defoamer BYK-141, leveling agent BYK-330, and SDBS. Methyl isopropyl ketone can effectively dissolve and uniformly disperse the polymer elastomer and the auxiliary, and the auxiliary can promote the contact between the polymer elastomer and the electromagnetic wave absorbing powder, improve the compatibility of the slurry, adjust the viscosity and fluidity, improve the coating property of the slurry, and increase the stability of the slurry.
[0033] In addition, in the above-mentioned method for preparing an electromagnetic wave absorbing material for an NFC antenna for a mobile phone, the electromagnetic wave absorbing powder is a soft magnetic composite material, and the preparation method includes the following steps S1 to S2: S1: Mixing an ammonium formate solution, a soft magnetic alloy powder, and aluminum sulfate, and ultrasonically dispersing the mixture for 10 to 3 minutes to obtain a mixed solution, heating the mixed solution in a water bath at 75 to 85°C, maintaining the mixture at that temperature and reacting it with stirring for 1 to 2 hours, washing the mixture with ethanol multiple times and magnetically separating the mixture, drying the mixture in an oven at 40 to 50°C for 1 to 3 days, and then annealing the mixture at 350 to 450°C for 2 hours to obtain a soft magnetic alloy powder coated with an Al2O3 layer; S2: The soft magnetic alloy powder coated with the Al2O3 layer is spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, heated to 400°C at 3-6°C / min under an argon protective atmosphere with a gas flow rate of 50-100mL / min, and then acetylene gas is introduced at a flow rate of 20-30mL / min to react for 0.5-1 hour. After the reaction is completed, the acetylene gas is stopped, the material is slowly cooled to 25°C, and taken out to obtain a soft magnetic composite material.
[0034] First, an Al2O3 layer is coated on the surface of the soft magnetic alloy powder by the sol-gel method, and then an amorphous carbon layer is introduced on the surface of the soft magnetic alloy by the CCDV method. The highly resistive amorphous carbon layer can reduce the dielectric constant of the magnetic metal, achieve good impedance matching between the absorbing material and free space, and improve the microwave absorption properties and corrosion resistance. Effect of the Invention
[0035] Compared with the prior art, the present invention has the following advantageous effects: (1) The NFC antenna for mobile phone disclosed in the present invention has an electromagnetic wave absorbing layer between the NFC antenna body and the metal base plate. The electromagnetic wave absorbing layer is thin, lightweight, and has strong magnetic shielding performance, which can effectively shield the NFC antenna from metal interference and ensure the signal quality of the NFC antenna. (2) In the NFC antenna for mobile phones disclosed by the present invention, the electromagnetic wave absorbing powder is mixed with the polymer elastomer in a flatly spread manner, thereby forming a uniform particle size distribution and making it easy to process into electromagnetic wave absorbing materials of various shapes. The polymer elastomer acts as a filler and binder in the electromagnetic wave absorbing material, uniformly dispersing the electromagnetic wave absorbing powder in the electromagnetic wave absorbing material and improving the magnetic shielding effect. In addition, the electromagnetic wave absorbing powder can be tightly bonded to the polymer elastomer to increase the mechanical strength and stability of the electromagnetic wave absorbing material, thereby realizing high magnetic permeability, good impedance matching, stable electromagnetic wave absorption and high reliability. (3) The soft magnetic composite material of the NFC antenna for mobile phones disclosed in the present invention uses a two-dimensional sheet-like multi-layer structure, in which an Al2O3 layer is provided between the soft magnetic alloy and the amorphous carbon layer, which not only prevents the generation of carbon nanomaterials on the surface of the soft magnetic composite material, but also introduces a multiple scattering and reflection mechanism to improve the microwave absorption properties, and at the same time, this multi-layer structure can act as a shielding protection and improve the corrosion resistance of the soft magnetic composite material. (4) The preparation method of the electromagnetic wave absorbing material for NFC antennas for mobile phones disclosed by the present invention is less expensive than ferrite, and the electromagnetic wave absorbing material produced by the above preparation method is a flexible product, can be designed into various shapes, does not shed, does not require edging or double-sided coating, and can reduce the process and cost. [Brief description of the drawings]
[0036] [Figure 1] 1 is a schematic diagram of an NFC antenna for a mobile phone according to the present invention. [Diagram 2]FIG. 1 is a cross-sectional view of a soft magnetic composite material of an NFC antenna for a mobile phone according to the present invention. [Diagram 3] 1 is a cross-sectional SEM image of an electromagnetic wave absorber according to Example 1 of the present invention. [Figure 4] 4 is a cross-sectional SEM image of an electromagnetic wave absorber according to Example 2 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] Hereinafter, the technical means in the embodiments of the present invention will be described clearly and in detail with reference to Example 1, Example 2, Comparative Example 1, Example 3, Example 4, specific test data, and Figures 1 to 4, but it goes without saying that the embodiments described are only some of the embodiments of the present invention and do not include all of the embodiments. All other embodiments obtained by those skilled in the art on the basis of the embodiments of the present invention without any creative activity are all within the scope of protection of the present invention.
[0038] The following Examples 1 and 2 provide electromagnetic wave absorbing materials, and the raw materials used in Examples 1 and 2 are commercially available raw materials commonly used in industry.
[0039] Example 1 The electromagnetic wave absorber of Example 1 includes a soft magnetic alloy and a polymer elastomer, the soft magnetic alloy is a sendust alloy, and the polymer elastomer is polyurethane. The preparation method includes the following steps: S1 raw material blending: a process of uniformly blending sendust alloy powder and polyurethane to obtain a raw material blend having a mass ratio of sendust alloy powder to polyurethane of 85:15; S2 slurry stirring: adding the raw material mixture to a stirrer, then adding methyl isopropyl ketone, dispersant BYK-110, antifoaming agent BYK-141, leveling agent BYK-330, SDBS, mixing the raw material mixture, methyl isopropyl ketone, dispersant BYK-110, antifoaming agent BYK-141, leveling agent BYK-330, SDBS in a mass ratio of 100:150:1:0.8:0.5:0.3:0.3, and stirring thoroughly until homogeneous to produce a slurry; S3 Slurry coating: The slurry is coated on a protective film, and spread evenly on the protective film surface with a scraper. The coating temperature is set to 100°C and the speed is set to 1m / min, and a dry film is obtained after drying. S4 Dry film lamination: The dried film is put into a laminator, and the temperature is set to 160°C and the pressure is set to 15Mpa to densify it to form an electromagnetic wave absorbing material; and S5 Cutting: The process of cutting the laminated electromagnetic wave absorbing material according to the design requirements to obtain the required size and shape.
[0040] Example 2 The electromagnetic wave absorber of Example 2 includes a soft magnetic composite material and a polymer elastomer, and polyurethane is used as the polymer elastomer. The preparation method includes the following steps: Preparation of S1 soft magnetic composite material: Add 12.612g of ammonium formate powder to 1L of deionized water solution, and after dispersion, add formic acid solution to adjust the pH to 4.4 to obtain ammonium formate solution. Mix ammonium formate solution, soft magnetic alloy powder, and aluminum sulfate in a mass ratio of 506:6:3, and ultrasonically disperse for 15 minutes to obtain a mixed solution. Heat this mixed solution to 75°C in a water bath, keep it at that temperature, and react with stirring for 1.5 hours. Wash with ethanol multiple times and magnetically separate, then dry in an oven at 45°C for 23 days. Then, anneal at 380℃ for 2 hours to obtain soft magnetic alloy powder coated with Al2O3 layer. The soft magnetic alloy powder coated with Al2O3 layer is spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, heated to 400℃ at 5℃ / min under argon protective atmosphere with gas flow rate of 50-100mL / min, and then acetylene gas is introduced at a flow rate of 25mL / min to react for 1 hour to generate an amorphous carbon layer. After the reaction is completed, the acetylene gas is stopped and the material is slowly cooled to 25℃ and taken out to obtain a soft magnetic composite material. As shown in Figure 2, the soft magnetic composite material includes, from the inside to the outside, a soft magnetic alloy a, an Al2O3 layer b, and an amorphous carbon layer c. S2 raw material blending: A process of uniformly blending soft magnetic composite material and polyurethane to obtain a raw material blend with a mass ratio of soft magnetic composite material to polyurethane of 88:12; S3 slurry stirring: adding the raw material mixture to a stirrer, then adding methyl isopropyl ketone, dispersant BYK-110, antifoaming agent BYK-141, leveling agent BYK-330, SDBS, mixing the raw material mixture, methyl isopropyl ketone, dispersant BYK-110, antifoaming agent BYK-141, leveling agent BYK-330, SDBS in a mass ratio of 100:145:0.8:0.8:0.6:0.4:0.3, and stirring thoroughly until homogeneous to produce a slurry; S4 Slurry application: The slurry is applied onto the protective film and spread evenly on the protective film surface with a scraper, and the temperature of the application is set to 105°C and the speed is set to 1m / min; S5 Dry film lamination: The dried film is put into a laminator, and the temperature is set to 165°C and the pressure is set to 15Mpa to rapidly dry the film to form an electromagnetic wave absorbing material; and S6 Cutting: The process of cutting the laminated electromagnetic wave absorbing material according to the design requirements to obtain the required size and shape.
[0041] Measurement of electromagnetic wave absorption characteristics: The electromagnetic parameters of the sendust alloy of Example 1 and the soft magnetic composite material of Example 2 were measured. The measuring device was a vector analyzer, and the measurement frequency band was 0.5 to 18 GHz.
[0042] For the measurements, the Sendust alloy of Example 1 and the soft magnetic composite material of Example 2 were made into a coaxial ring and measured; that is, paraffin, the Sendust alloy of Example 1, and the soft magnetic composite material of Example 2 were thoroughly mixed in a mass ratio of 1:1 until homogeneous, and a coaxial ring with a thickness of approximately 2.5 mm, an inner diameter of approximately 3.0 mm, and an outer diameter of approximately 7.0 mm was produced.
[0043] Measurement results of electromagnetic wave absorption properties: Generally speaking, when RL<-10 dB, the material is considered to have an effective electromagnetic wave absorption bandwidth. In the frequency range of 0.5-18.0 GHz, the RL value of the sendust alloy of Example 1 is less than -10 dB in a bandwidth of less than 0.2 GHz, which indicates that the sendust alloy of Example 1 has a large limit in practical use. The soft magnetic composite material of Example 2 has an RLmin of -23.9 dB at 6.8 GHz, and the effective electromagnetic wave absorption bandwidth can reach 3.4 GHz.
[0044] The above-mentioned electromagnetic wave absorption property measurement results show that the two-dimensional sheet-like multilayer structure of the soft magnetic composite material synthesized by first coating Al2O3 by the sol-gel method and then coating an amorphous carbon layer by the CCDV method has significantly improved minimum microwave loss value RLmin and effective bandwidth, etc., compared with the two-dimensional sheet-like single-layer structure of the Sendust alloy in Example 1, and the electromagnetic wave absorption properties of the electromagnetic wave absorbing powder have been greatly improved.
[0045] SEM characteristic evaluation: SEM characteristic evaluation is performed on the electromagnetic wave absorbers of Examples 1 and 2. From Figures 3 and 4, it can be seen that the electromagnetic wave absorbers of Examples 1 and 2 are both made by laminating electromagnetic wave absorbing powders having a two-dimensional sheet-like structure and laying them flat, and that the electromagnetic wave absorbing powders are blocked by interposing a polymer elastomer between the electromagnetic wave absorbing powders, so that the electromagnetic wave absorbing powders do not conduct electricity. The surfaces of the electromagnetic wave absorbing powders in the electromagnetic wave absorbers of Examples 1 and 2 are smooth and irregularly flaky in shape, which shows that the soft magnetic composite material coated by the sol-gel method and the CCVD method has a good enveloping effect and can maintain the stability of the basic shape.
[0046] Measurement of magnetic permeability and inductance value: Referring to GB / T32596, the magnetic permeability and inductance values of the electromagnetic wave absorbers of Examples 1 and 2 were measured. The thicknesses were 0.1 mm and 0.08 mm, respectively. The measurement results are shown in Table 1.
[0047] [Table 1]
[0048] From Table 1, it can be seen that when the thickness is approximately 0.08 mm, the permeability of Examples 1 and 2 is 221.4 and 220.5, respectively, and the inductance values are 368 μH and 353 μH, respectively, and when the thickness is approximately 0.1 mm, the permeability of Examples 1 and 2 is 151.2 and 150.7, respectively, and the inductance values are 365 μH and 352 μH, respectively.
[0049] Measurement of corrosion resistance: The electrochemical corrosion parameters were calculated using the electrochemical corrosion analysis method, the measuring device was an electrochemical workstation, and the measurement process used a three-electrode system, the reference electrode was a silver chloride electrode, the auxiliary electrode was a platinum electrode, and samples 1 to 4 were placed on copper foil to prepare the working electrode, and the measurement results are shown in Table 2.
[0050] [Table 2]
[0051] From Table 2, the electromagnetic wave absorbing material of Example 1 uses a sendust alloy as the electromagnetic wave absorbing powder, and its natural corrosion potential E corr are -0.31V and -0.33V, respectively, and the corrosion current density i corr are 5.12×10 ‐6 A / cm 2 , 5.12×10 ‐6 A / cm 2 and the polarization resistance Rp is 1.75×10 5 Ω / cm 2 , 1.97×10 5 Ω / cm2 and the corrosion rate CR is 1.87×10 ‐12 m / s, 2.03×10 ‐12 The electromagnetic wave absorbing material of Example 2 uses a sendust alloy coated with an Al2O3 layer and an amorphous carbon layer as the electromagnetic wave absorbing powder, and its natural corrosion potential E corr increases to -0.05V and -0.04V, and the corrosion current density i corr is 1.12 × 10 ‐6 A / cm2 , 1.08×10 ‐6 A / cm 2 The polarization resistance Rp drops to 9.74×10 5 Ω / cm 2 , 19.82×10 5 Ω / cm 2 and the corrosion rate CR is 2.98×10 ‐13 m / s, 3.01×10 ‐13 m / s, which indicates that the electromagnetic wave absorber of Example 2 has better corrosion resistance and can have a better life in various environments.
[0052] The following Comparative Example 1, Example 3, Example 4, Example 5, and Example 6 provide NFC antennas for mobile phones. The materials used in Comparative Example 1, Example 3, Example 4, Example 5, and Example 6 were commercially available raw materials commonly used in industry.
[0053] Comparative Example 1 The NFC antenna for a mobile phone of Comparative Example 1 comprises an NFC antenna main body 1 and a metal bottom plate 3, the coil inductance value of the NFC antenna main body 1 being 1.7 μH and the sensing distance being 3.67 mm, and the metal bottom plate 3 being made of aluminum foil material (simulating a battery exterior material) having a thickness of 0.05 mm, and the NFC antenna main body 1 and the metal bottom plate 3 being assembled to obtain the NFC antenna for a mobile phone of Comparative Example 1.
[0054] Example 3 As shown in FIG. 1 , the NFC antenna for a mobile phone of Example 3 comprises an NFC antenna main body 1, an electromagnetic wave absorbing material layer 2, and a metal bottom plate 3, the coil inductance value of the NFC antenna main body 1 is 1.7 μH, the sensing distance is 3.67 mm, the electromagnetic wave absorbing material layer 2 is made of the electromagnetic wave absorbing material of Example 1 and has a thickness of about 0.08 mm, and the metal bottom plate 3 is made of an aluminum foil material with a thickness of 0.05 mm, and the NFC antenna main body 1, the electromagnetic wave absorbing material layer 2, and the metal bottom plate 3 are assembled in this order to obtain the NFC antenna for a mobile phone of Example 3.
[0055] Example 4 As shown in FIG. 1 , the NFC antenna for a mobile phone of Example 4 comprises an NFC antenna main body 1, an electromagnetic wave absorbing material layer 2, and a metal bottom plate 3, the coil inductance value of the NFC antenna main body 1 is 1.7 μH, the sensing distance is 3.67 mm, the electromagnetic wave absorbing material layer 2 is made of the electromagnetic wave absorbing material of Example 1 and has a thickness of about 0.1 mm, and the metal bottom plate 3 is made of an aluminum foil material with a thickness of 0.05 mm, and the NFC antenna main body 1, the electromagnetic wave absorbing material layer 2, and the metal bottom plate 3 are assembled in this order to obtain the NFC antenna for a mobile phone of Example 4.
[0056] Example 5 As shown in FIG. 1 , the NFC antenna for a mobile phone of Example 5 comprises an NFC antenna main body 1, an electromagnetic wave absorbing material layer 2, and a metal bottom plate 3, the coil inductance value of the NFC antenna main body 1 is 1.7 μH, the sensing distance is 3.67 mm, the electromagnetic wave absorbing material layer 2 is made of the electromagnetic wave absorbing material of Example 2 and has a thickness of about 0.08 mm, and the metal bottom plate 3 is made of an aluminum foil material with a thickness of 0.05 mm, and the NFC antenna main body 1, the electromagnetic wave absorbing material layer 2, and the metal bottom plate 3 are assembled in this order to obtain the NFC antenna for a mobile phone of Example 5.
[0057] Example 6 As shown in FIG. 1 , the NFC antenna for a mobile phone of Example 6 comprises an NFC antenna main body 1, an electromagnetic wave absorbing material layer 2, and a metal bottom plate 3, the coil inductance value of the NFC antenna main body 1 is 1.7 μH, the sensing distance is 3.67 mm, the electromagnetic wave absorbing material layer 2 is made of the electromagnetic wave absorbing material of Example 2 and has a thickness of about 0.1 mm, and the metal bottom plate 3 is made of an aluminum foil material with a thickness of 0.05 mm, and the NFC antenna main body 1, the electromagnetic wave absorbing material layer 2, and the metal bottom plate 3 are assembled in that order to obtain the NFC antenna for a mobile phone of Example 6.
[0058] Antenna test: Refer to ISO / IEC14443, and use LCR100kHz for the digital bridge. The test results are shown in Table 3.
[0059] [Table 3]
[0060] The coil inductance value of the NFC antenna body 1 was 1.7 μH and the sensing distance was 3.67 mm. As can be seen from Table 3, when the NFC antenna body 1 and metal bottom plate 3 were assembled (Comparative Example 1), the metal bottom plate 3 interfered with the NFC signal because metal reflects and absorbs radio waves, and the inductance value decreased to 1.58 μH and the sensing distance decreased to 1.01 mm.
[0061] An electromagnetic wave absorbing layer 2 is provided between the NFC antenna main body 1 and the metal bottom plate 3 (Examples 3 to 5), and all of Examples 3 to 5 can effectively isolate the interference of the metal bottom plate 3 with the NFC antenna main body 1, thereby improving the signal quality of the NFC antenna main body 1. The inductance values of Examples 5 and 6, which use the electromagnetic wave absorbing material of Example 2, are 1.71 μH and 1.73 μH, respectively, which are close to the coil inductance value of the NFC antenna main body 1, and the sensing distances are 3.56 mm and 3.52 mm, respectively, which are close to the sensing distance of the NFC antenna main body 1, which indicates that Examples 5 and 6 have better matching between the NFC antenna main body 1 and the metal bottom plate 3 and have better magnetic shielding and electromagnetic wave absorption effects.
[0062] The specific applications of the present invention are numerous, and the above are merely preferred embodiments of the present invention. It should be noted that the above examples are only used to interpret the present invention, and are not intended to limit the scope of protection of the present invention. Those skilled in the art can make some improvements without departing from the principle of the present invention, and these improvements should also be considered as the scope of protection of the present invention. [Explanation of symbols]
[0063] 1 NFC antenna body 2 Electromagnetic wave absorbing layer 3 Metal bottom plate a Soft magnetic alloy b Al2O3 layer c Amorphous carbon layer
Claims
1. An NFC antenna for a mobile phone, comprising an NFC antenna main body (1), an electromagnetic wave absorbing material layer (2), and a metal bottom plate (3), the electromagnetic wave absorbing material layer (2) being provided on the metal bottom plate (3), the NFC antenna main body (1) being provided on the electromagnetic wave absorbing material layer (2), the electromagnetic wave absorbing material layer (2) being a film or sheet made of an electromagnetic wave absorbing material, the electromagnetic wave absorbing material including an electromagnetic wave absorbing powder and a polymer elastomer, the electromagnetic wave absorbing powder being a soft magnetic alloy or a soft magnetic composite material, having a two-dimensional sheet-like structure, and being spread evenly within the polymer elastomer, the mass ratio of the electromagnetic wave absorbing powder to the polymer elastomer being 10-20:1-5, the soft magnetic composite material being, from the inside to the outside, a soft magnetic alloy, Al 2 O 3 The NFC antenna for a mobile phone is characterized in that it has a two-dimensional sheet-like multilayer structure including a carbon layer and an amorphous carbon layer.
2. 2. The NFC antenna for a mobile phone according to claim 1, wherein the electromagnetic wave absorbing powder has a powder thickness of 0.5 to 1.5 μm and a particle diameter D50 range of 30 to 100 μm.
3. 2. The NFC antenna for a mobile phone according to claim 1, wherein the soft magnetic alloy is at least one selected from the group consisting of an iron-silicon-aluminum soft magnetic alloy, an iron-silicon soft magnetic alloy, an iron-nickel soft magnetic alloy, an iron-nickel-molybdenum soft magnetic alloy, an iron-aluminum soft magnetic alloy, an iron-silicon-aluminum-nickel soft magnetic alloy, an iron-chromium soft magnetic alloy, and an iron-cobalt soft magnetic alloy.
4. 2. The NFC antenna for a mobile phone according to claim 1, wherein an inductance value of the antenna coil of the NFC antenna body (1) is 1.6 to 2.0 μH.
5. 2. The NFC antenna for a mobile phone as described in claim 1, wherein the electromagnetic wave absorbing material is formed by stacking and laying out the electromagnetic wave absorbing powder having a two-dimensional sheet-like structure, and the polymer elastomer is interposed between the electromagnetic wave absorbing powder to block the electromagnetic wave absorbing powder from passing through the powder, thereby preventing electrical continuity of the electromagnetic wave absorbing powder.
6. The NFC antenna for a mobile phone according to claim 1 , wherein the polymer elastomer is at least one of polyurethane, acrylic acid, organosilicon, and epoxy resin.
7. A method for preparing an electromagnetic wave absorbing material for an NFC antenna for a mobile phone according to any one of claims 1 to 6, comprising the steps of: Bulk density 0.2 to 0.7 g / cm 3 , tap density 0.6 to 2.0 g / cm 3 A raw material blending step S1 in which the electromagnetic wave absorbing powder and the polymer elastomer are uniformly mixed to obtain a raw material mixture; A slurry stirring step S2 in which the raw material mixture is added into a stirrer, a solvent and an auxiliary component are then added, and the solvent, the raw material mixture and the auxiliary component are mixed in a mass ratio of 40 to 80: 10 to 50: 0.5 to 2, and the mixture is thoroughly stirred until homogenous, to produce a slurry having a viscosity of 1500 to 2000 mPa s; a slurry application step S3 in which the slurry is applied onto a protective film, spread evenly over the protective film surface with a scraper, and the application temperature is set to 50 to 120° C. and the speed is set to 0.5 to 4 m / min, and a dried film is obtained after drying; A dry film lamination process S4 in which the dried film is placed in a laminator, and the temperature is set to 150 to 180° C. and the pressure is set to 10 to 20 MPa to densify the film to form an electromagnetic wave absorbing material; A die-cutting process S5 in which the laminated electromagnetic wave absorbing material is cut according to design requirements to obtain the required size and shape; A method for preparing an electromagnetic wave absorbing material for an NFC antenna for a mobile phone, comprising:
8. The method for preparing an electromagnetic wave absorbing material for an NFC antenna for a mobile phone according to claim 7, characterized in that the solvent in S2 is any one of methyl isopropyl ketone, acetone, cyclohexanone, and DMF, and the auxiliary component is at least one of a dispersant, a defoamer, a leveling agent, and a surfactant.
9. The electromagnetic wave absorbing powder is a soft magnetic composite material, and the preparation method thereof comprises the steps of: Ammonium formate solution, soft magnetic alloy powder, and aluminum sulfate are mixed and ultrasonically dispersed for 10 to 3 minutes to obtain a mixed solution, the mixed solution is heated in a water bath at 75 to 85°C, and is reacted while being kept at that temperature for 1 to 2 hours while being stirred. After washing with ethanol several times and magnetic separation, it is dried in an oven at 40 to 50°C for 1 to 3 days, and then annealed at 350 to 450°C for 2 hours to obtain Al. 2 O 3 A step S1 of obtaining a soft magnetic alloy powder coated with a layer; The Al 2 O 3 The soft magnetic alloy powder coated with the layer is spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, heated to 400° C. at 3-6° C. / min under an argon protective atmosphere with a gas flow rate of 50-100 mL / min, and then reacted for 0.5-1 hour by introducing acetylene gas at a flow rate of 20-30 mL / min. After the reaction is completed, the acetylene gas is stopped, the material is slowly cooled to 25° C., and the material is taken out to obtain the soft magnetic composite material. The method for preparing the electromagnetic wave absorbing material of the NFC antenna for a mobile phone according to claim 7, comprising:
Citation Information
Patent Citations
Compound magnetic conductive plate used for wireless charging and near field communication and preparation method thereof
CN105336465A
Soft magnetic alloy powder, wave absorption sheet, preparation method of soft magnetic alloy powder, electronic component and electronic equipment
CN110060834A
Multifunctional leather sheath for mobile phone
CN206949752U
Antenna and radio communication device
JP2014200031A
NFC antenna and tag
CN217983663U